1998
DOI: 10.1002/(sici)1521-4044(199809)49:9<482::aid-apol482>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

On the nodular morphology and mechanical behavior of a syntactic foam cured in thermal and microwave fields

Abstract: The morphology of a syntactic foam (hollow microspheres in a polymeric matrix) is differently affected when cured in thermal and microwave fields. The microwave curing energy excludes heat conduction and due to faster energy transfer more efficient crosslinking effects are observed at the interface, leading to a higher internodular crosslink density at the particle interface. As a consequence, slight but observable differences of mechanical behavior arise when curing the hollow glass microsphere filled epoxy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
(19 reference statements)
2
6
0
Order By: Relevance
“…Palumbo et al [61] showed that the morphology of a syntactic foam (hollow microspheres in a polymeric matrix) could be changed when cured under thermal and microwave conditions.…”
Section: The Role Of Fillers In Polymer Composites and Hybrid Materialsmentioning
confidence: 99%
“…Palumbo et al [61] showed that the morphology of a syntactic foam (hollow microspheres in a polymeric matrix) could be changed when cured under thermal and microwave conditions.…”
Section: The Role Of Fillers In Polymer Composites and Hybrid Materialsmentioning
confidence: 99%
“…Foams were then cured further by incubation at 100°C in a convection oven. Curing continues the polymerization/crosslinking reactions and is often peripheral to the actual manufacturing process, normally additives or thermal cooking is employed to control the rate of plastic curing in order to obtain a more satisfactory thermoset plastic [27]. Thermal curing is often conducted to complete the polymerization process and stabilize the polymers physical characteristics [28][29][30].…”
Section: Physical Changes In Glycerol Citrate Polyestersmentioning
confidence: 99%
“…Thermal curing is often conducted to complete the polymerization process and stabilize the polymers physical characteristics [28][29][30]. Heat curing of plastic polymers by thermal or microwave treatments often results in polymers with distinctly different physical characteristics [27,30]. By regulating the speed by which plastic polymer hardens and sets, through either heating and/or curing additives plastic manufacturers increase the efficiency of their production methods [31].…”
Section: Physical Changes In Glycerol Citrate Polyestersmentioning
confidence: 99%
“…Unreinforced voids, also called interstitial or unwanted, are sometimes entrapped in the matrix during manufacturing, 3 while the interphase is a region of the matrix surrounding the inclusions with modified mechanical properties. This modification can be due to differential polymer curing in the proximity of the inclusions which may act as heat sinks (Palumbo and Tempesti, 1998). 4 Here, we extend and improve the FE MPUCs by:…”
Section: Introductionmentioning
confidence: 99%